Heavy Metal (Pb, Hg) Extent in Mud Crab (Scylla serrata) in Cengkok Coastal Waters, Banten Bay, Indonesia - Ertika Noviani; Sulistiono Sulistiono; Agustinus Mangaratua Samosir (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
Banten Bay is located in the north of Java Island and influenced by anthropogenic activities around the bay. Increasing population growth and rapid development of industrial and urban activities around the waters of the Banten Bay can lead to an increased input of pollutants in the form of heavy metal in the water body. This study aims to analyze the Pb and Hg levels that accumulate in mud crab (Scylla serrata) in Cengkok coastal waters, Banten Province. Samples of the mud crabs were taken in the waters for six months, from March to August 2019. Analysis of heavy metal concentrations was carried out using the Atomic Absorption Spectrophotometric (AAS) AA 7000 series Shimadzu. Heavy metal (Pb and Hg) in the mud crab in Banten Bay were below the specified quality standard. The bio-concentration factor of the mud crab was low (<100). Results of the calculation of the maximum limit of consumption of the mud crab meat (that accumulates heavy metals in the human body) were 3.5 kg of meat/week for adults and 0.9 kg of meat/week for children.Keywords: Crustacean, pollution, limit of consumption.